Clinical manifestations of treatment tolerance disorders in patients with primary open-angle glaucoma - V.E. Korelina; Z.M. Nagornova; I.A. Bulakh; A.V. Kuroyedov; D.A. Baryshnikova; A.B. Galimova; A.M. Getmanova; V.V. Gorodnichiy; S.A. Zubasheva; U.R. Karimov; S.V. Kosmynina; E.B. Parova; et al. (РМЖ "Клиническая офтальмология")
Clinical manifestations of treatment tolerance disorders in patients with primary open-angle glaucoma V.E. Korelina1, Z.M. Nagornova2, I.A. Bulakh3, A.V. Kuroyedov4,5, D.A. Baryshnikova6, A.B. Galimova7, A.M. Getmanova8, V.V. Gorodnichy5, S.A. Zubasheva9, U.R. Karimov10, S.V. Kosmynina11, E.B. Parova4, A.V. Seleznev2, I.I. Semenova12, T.V. Chernyakova4,13, A.P. Shakhalova14 (Scientific Avant-garde Research Group of the Russian Glaucoma Society, 2011–2023©) 1North West State Medical University named after I.I. Mechnikov, St. Petersburg,   Russian Federation 2Ivanovo State Medical University, Ivanovo, Russian Federation 3Ivastramed Medical Center LLC, Ivanovo, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation 5P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 6Sectoral Clinical Diagnostic Center of the Gazprom PJSC, Moscow, Russian Federation 7Bashkir State Medical University, Ufa, Russian Federation 8Bryansk Regional Hospital No. 1, Bryansk, Russian Federation 9Treatment and Diagnostic Center No. 9, Moscow, Russian Federation 10Syr Darya Regional Ophthalmic Hospital, Gulistan, Republic of Uzbekistan 11Pavlov-Med LLC, Murmansk, Russian Federation 12Mogilev City Hospital of the Emergency Medical Care, Mogilev, Republic of Belarus 1352 Advisory and Diagnostic Center of the Ministry of Defense of the Russian Federation,   Moscow, Russian Federation 14Tonus Amaris Medical Clinical Center, Nizhny Novgorod, Russian Federation Aim: to determine the clinical manifestations of treatment tolerance disorders in patients with primary open-angle glaucoma (POAG) with different duration of the disease, timing and treatment regimens. Patients and Methods: the final protocol of the cohort scientific clinical combined multicenter study included the case monitoring results in 115 patients (115 eyes) with advanced and severe stages of POAG; according to duration of the verified medical history, they were divided into two groups: 0.72 [0.32; 0.92] and 2.7 [1.9; 3.8] years. The indicators and characteristics (age, the disease stage, medical history, intraocular pressure level, hypotensive regimen and treatment satisfaction according to the Treatment Satisfaction Survey for Intraocular Pressure/TSS-IOP questionnaire) that may represent POAG treatment efficacy and tolerability criteria were studied. Results: age, intraocular pressure (IOP) level at the diagnosis verification timepoint and final examination in POAG patients were comparable in both groups. In spite of a significant decrease in IOP level due to local hypotensive therapy, morphometric parameters decreased. Patients experienced from one to five changes of treatment regimens. This was associated with both the IOP level and morphometric changes. The maximum hypotensive therapy was the most efficient and longest one, while monotherapy with beta-blockers showed the worst efficiency. TSS-IOP data analysis showed that, despite local adverse effects of antiglaucoma therapy, visual functions is a priority for the majority of patients. Conclusion: the study showed that tolerance to POAG treatment develops in a large number of patients at a fairly early stage. Initial monotherapy becomes ineffective in 79.6% of patients during the first six months of the treatment. A stepwise (conventional) approach to hypotensive glaucoma therapy is ineffective in patients with advanced and severe stages of POAG. The longer antihypertensive treatment duration, the more changes in local hypotensive therapy regimens were performed. Keywords: glaucoma, intraocular pressure, tolerance, duration of treatment, maximum hypotensive therapy. For citation: Korelina V.E., Nagornova Z.M., Bulakh I.A., Kuroyedov A.V., Baryshnikova D.A., Galimova A.B., Getmanova A.M., Gorodnichy V.V., Zubasheva S.A., Karimov U.R., Kosmynina S.V., Parova E.B., Seleznev A.V., Semenova I.I., Chernyakova T.V., Shakhalova A.P. (Scientific Avantgarde Research Group of the Russian Glaucoma Society, 2011–2023©). Clinical manifestations of treatment tolerance disorders in patients with primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2024;24(4):159–169 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-1